Pengaruh Exhaust Gas Cleaning System Gas Buang Yang Gagal Dimurnikan (Di Kapal MV Cosmo Gloria) - priyanto, priyanto; Jayamahendra, Mohamad Alfadin (Marine Science and Technology Journal, 2024)
Starting January 1 2020, IMO implemented a low sulfur/low sulfur emission standard which applies to fuel oil used by ships, emission control is regulated by not exceeding 0.5% sulfur content in exhaust gas. To comply with these regulations, the Toei Korea company chose to use a new type of tool called a scrubber which is a tool for separating solid particles (dust) in the exhaust gas by using liquid as a tool which aims to reduce the sulfur content contained in the exhaust gas. This research aims to analyze whether EGCS (Exhaust Gas Cleaning System) is a factor that influences exhaust gas purification. This research also tested and analyzed the effect of EGCS (Exhaust Gas Cleaning System) on exhaust gas that failed to be purified in Mv. Cosmo Gloria EGCS (Exhaust Gas Cleaning System) is a device installed on marine vessels that literally "scrubs" harmful sulfur oxides from exhaust gases. This technology is usually installed on ships that are looking for compliance options in the face of stricter emissions. Efforts are made to carry out routine and periodic system maintenance plans, which in turn can reduce similar incidents on board ships. From this problem it can be concluded that maintenance on the lazer gas analyzer on the EGCS (Exhaust Gas Cleaning System) needs to be carried out regularly and in accordance with the instruction manual book created, so that problems can be identified as early as possible and prevent greater damage.